Migrációs folyamatok vizsgálata Mezőhegyesen: 1989-2008 - Zsótér, Brigitta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The main characteristics of the migration in connection with Mezőhegyes between 1989 and 2008 are the following: to put every result together there is a loss in migration in the examined period; the proportion of men and women involved in migration is approximately the same; the balance is negative in case of the young and the middle-aged; the proportion of people aged 30-44 and 45-59 is the highest; the intraregional migration dominates; 61% of the entire migration of the settlements take place within the borders of coun-ties Békés and Csongrád.